A case of herpes zoster developing after COVID-19 vaccine and recurring after COVID-19 infection in the same dermatome - Sevgi Kulaklı; Işıl Deniz Oguz; Burak Akşan (Galenos Publishing House, 2023)
Coronavirus disease-2019 (COVID-19) is an ongoing infectious respiratory disease recognized worldwide as a pandemic, and it can affect many organs and systems, including the skin. Various cutaneous manifestations, including reactivation of varicella-zoster virus related to COVID-19 and COVID-19 vaccination have been reported. We would like to present a 46-year-old female, who developed herpes zoster (HZ) in the right C3 dermatome after m-RNA COVID-19 vaccine and was admitted to our clinic with recurrent HZ in the same dermatome following COVID-19 infection, two months after the vaccination.